2010
DOI: 10.1186/1472-684x-9-9
|View full text |Cite
|
Sign up to set email alerts
|

Destined to die in hospital? Systematic review and meta-analysis of place of death in haematological malignancy

Abstract: BackgroundHaematological malignancies are a common, heterogeneous and complex group of diseases that are often associated with poor outcomes despite intensive treatment. Research surrounding end-of-life issues, and particularly place of death, is therefore of paramount importance, yet place of death has not been formally reviewed in these patients.MethodsA systematic literature review and meta-analysis was undertaken using PubMed to identify all studies published between 1966 and 2010. Studies examining place … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 35 publications
(40 reference statements)
8
77
0
Order By: Relevance
“…Amid the growing literature showing that patients with blood cancers have inadequate access to palliative care services, 19,23,[34][35][36] our findings have three important implications. First, targeted education about a more inclusive role for palliative care in hematologic oncology is needed.…”
Section: 33mentioning
confidence: 97%
See 1 more Smart Citation
“…Amid the growing literature showing that patients with blood cancers have inadequate access to palliative care services, 19,23,[34][35][36] our findings have three important implications. First, targeted education about a more inclusive role for palliative care in hematologic oncology is needed.…”
Section: 33mentioning
confidence: 97%
“…Patients with hematologic malignancies have significant palliative care needs, including high symptom burden [15][16][17] ; however, they remain less likely than patients with solid tumors to receive specialist palliative care services and more likely to receive aggressive health care at the end of life. 18 Specifically, patients with blood cancers are less frequent users of hospice services, 19 less likely to be seen by consultative palliative care services in the hospital, 20 more likely to die in a hospital or intensive care unit, [21][22][23] and more likely to receive chemotherapy in the last few weeks of life. 24 These findings point toward unmet palliative care needs in the hematologic malignancy population.…”
mentioning
confidence: 99%
“…Cancer diagnoses were grouped using the categories in Canadian Cancer Statistics 2017 9 , which uses the International Classification of Diseases for Oncology (3rd edition). For the present study, the focus was on the four most frequent diagnoses (breast, prostate, colorectal, and lung cancer) 9 ; two other diagnoses with high mortality rates (pancreatic and esophageal cancer) 9 ; a complex, high-needs diagnosis (head-and-neck cancer) 24 ; and hematologic cancers for which the time of death is more difficult to predict 25 …”
Section: Variablesmentioning
confidence: 99%
“…22 Additional studies involving nonpopulation-based samples have identified many additional place influences, including the length of the dying process, and pain or other symptoms. 23,24 Objective A population-based survey was conducted to examine public preferences for place of last days of life and answer three questions:…”
Section: Literature Reviewmentioning
confidence: 99%